2015
DOI: 10.1186/s12885-015-1748-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence persistence or recurrence of high-grade squamous intraepithelial lesion with positive margins after the loop electrosurgical excision procedure: a retrospective study

Abstract: BackgroundIn 5–20 % of patients with cervical high-grade squamous intraepithelial lesion (HSIL), a positive margin after the loop electrosurgical excision procedure (LEEP) is associated with persistence/recurrence, but the prognostic value of other clinico-pathological factors is less clear.MethodsAmong 4336 patients with HSIL who underwent an initial LEEP, 275 (6 %) had HSIL-positive margins, 37 of whom were lost to follow-up. We evaluated the remaining 238 patients. Persistence/recurrence was defined as hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
2
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
3
20
2
2
Order By: Relevance
“…This was in contrast to the findings of Zhu et al, 17 The present study showed that 12.5% of the endocervical margin was affected, which is significantly lower than the 24.1% described by Venegas-Rodríguez et al 18 In the present study, the affected endocervical margin was found to be a risk factor for pathological cytology presenting at 6 months post-treatment, which increased the risk by three times compared to the non-affected endocervical margin. This was in contrast to the findings of Zhu et al, 17 The present study showed that 12.5% of the endocervical margin was affected, which is significantly lower than the 24.1% described by Venegas-Rodríguez et al 18 In the present study, the affected endocervical margin was found to be a risk factor for pathological cytology presenting at 6 months post-treatment, which increased the risk by three times compared to the non-affected endocervical margin.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…This was in contrast to the findings of Zhu et al, 17 The present study showed that 12.5% of the endocervical margin was affected, which is significantly lower than the 24.1% described by Venegas-Rodríguez et al 18 In the present study, the affected endocervical margin was found to be a risk factor for pathological cytology presenting at 6 months post-treatment, which increased the risk by three times compared to the non-affected endocervical margin. This was in contrast to the findings of Zhu et al, 17 The present study showed that 12.5% of the endocervical margin was affected, which is significantly lower than the 24.1% described by Venegas-Rodríguez et al 18 In the present study, the affected endocervical margin was found to be a risk factor for pathological cytology presenting at 6 months post-treatment, which increased the risk by three times compared to the non-affected endocervical margin.…”
contrasting
confidence: 99%
“…Zhu et al 17 which showed a recurrence of 11.3%, and higher than Venegas-Rodríguez et al 18 who described a 5.5% persistence rate.…”
mentioning
confidence: 83%
“…En el presente estudio se encontró un porcentaje de recurrencia/persistencia del 5,55%, estos datos son menores que los reportados por Zhu et al en el 2015 de 11.3% (10) . El tiempo promedio de presentación de la recurrencia/persistencia fue 21.4, contrario a los hallazgos encontrados por Skimer et al quien encontró que el 74% de los pacientes que presentaron recurrencia/persistencia fue dentro de los primeros 6 meses de seguimiento (12) .…”
Section: Discussionunclassified
“…A pesar de la efectividad del LEEP/ LLETZ, la recurrencia de NIC varía del 5 al 64% de los pacientes (4,5) . El 74% de los pacientes con NIC 2-3 tratados, presentan recurrencia en los primeros 6 meses (6,7) Múltiples estudios reportan persistencia o recurrencia de NIC en mujeres con márgenes comprometidos por la enfermedad (8)(9)(10) . La habilidad para interpretar los márgenes de escisión es un componente crítico para determinar el manejo óptimo de pacientes tratados por esta patología y se ha mostrado que aproximadamente 10 al 20% de los especímenes obtenidos por cono LEEP/LLETZ son totalmente imposibles de interpretar, aparentemente consecuencia del daño térmico causado.…”
Section: Introductionunclassified
“…Recurrence was defined as histology of CIN 1 or higher, which was diagnosed from a biopsy or a subsequent surgical (including LEEP) specimen at any time after the initial LEEP was conducted [14]. CIN 1 corresponded to mild dysplasia, CIN 2 to moderate dysplasia, and CIN 3 corresponded to both severe dysplasia and carcinoma in situ.…”
Section: Methodsmentioning
confidence: 99%